Allantoin catabolism influences the production of antibiotics in Streptomyces coelicolor - Navone, Laura (2014)
Purines are a primary source of carbon and nitrogen in soil; however, their metabolism is poorly understood in Streptomyces. Using a combination of proteomics, metabolomics, and metabolic engineering, we characterized the allantoin pathway in Streptomyces coelicolor. When cells grew in glucose minimal medium with allantoin as the sole nitrogen source, quantitative proteomics identified 38 enzymes upregulated and 28 downregulated. This allowed identifying six new functional enzymes involved in allantoin metabolism in S. coelicolor. From those, using a combination of biochemical and genetic engineering tools, it was found that allantoinase (EC 3.5.2.5) and allantoicase (EC 3.5.3.4) are essential for allantoin metabolism in S. coelicolor. Metabolomics showed that under these growth conditions, there is a significant intracellular accumulation of urea and amino acids, which eventually results in urea and ammonium release into the culture medium. Antibiotic production of a urease mutant strain showed that the catabolism of allantoin, and the subsequent release of ammonium, inhibits antibiotic production. These observations link the antibiotic production impairment with an imbalance in nitrogen metabolism and provide the first evidence of an interaction between purine metabolism and antibiotic biosynthesis.